Changes between Version 5 and Version 6 of u/johannjc/scratchpad5


Ignore:
Timestamp:
10/01/15 11:09:53 (9 years ago)
Author:
Jonathan
Comment:

Legend:

Unmodified
Added
Removed
Modified
  • u/johannjc/scratchpad5

    v5 v6  
    7878Now we can expand the derivatives and get
    7979
    80 $A \left ( \partial_i  B_{ij} \right ) \left ( C_\lambda  \partial_j T^{\lambda + 1} + D_\lambda  \partial_j T^{\lambda} T' \right ) + A B_{ij} \left ( C_\lambda  \partial_i \partial_j T^{\lambda + 1} + D_\lambda  \partial_i \partial_j T^{\lambda} T' \right ) $
     80$A \left ( \partial_i  B_{ij} \right ) \left ( C  \partial_j T^{\lambda + 1} + D  \partial_j T^{\lambda} T' \right ) + A B_{ij} \left ( C \partial_i \partial_j T^{\lambda + 1} + D  \partial_i \partial_j T^{\lambda} T' \right ) $
     81
     82and the whole equation is then
     83
     84$\partial_t T = \displaystyle \sum_{\parallel,\perp}{A \left ( \partial_i  B_{ij} \right ) \left ( C  \partial_j T^{\lambda + 1} + D  \partial_j T^{\lambda} T' \right ) + A B_{ij} \left ( C  \partial_i \partial_j T^{\lambda + 1} + D  \partial_i \partial_j T^{\lambda} T' \right )} $
     85
     86where $A$, $B$, $C$, $D$, and $\lambda$ are functions of $\perp,\parallel$
     87
     88We can also write this as
     89
     90$\partial_t T = \displaystyle \sum_{\parallel,\perp}{E \partial_j T^{\lambda + 1} + F \partial_j T^{\lambda} T' + G  \partial_i \partial_j T^{\lambda + 1} + H \partial_i \partial_j T^{\lambda} T'} $
     91
     92where
     93
     94$E = A \left ( \partial_i  B_{ij} \right ) C$
     95
     96$F =  A \left ( \partial_i  B_{ij} \right ) D$
     97
     98$G = A B_{ij} C$
     99
     100$H = A B_{ij} D$
    81101
    82102
    83 
    84 
    85 Let's first just consider the $\chi_\parallel$ term.
    86 
    87 $\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \kappa_\parallel T^\lambda \left ( \hat{b} \cdot \nabla T \right )\right ]$
    88 
    89 We need a way to write this implicitly but we need it to also be linear in $T_{*}$
    90 
    91 $\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \kappa_\parallel T_{*}^\lambda \left ( \hat{b} \cdot \nabla T_{*} \right )\right ]$
    92 
    93 We could Taylor expand $T^\lambda_{*}=T^\lambda + \lambda T^{\lambda-1} \left ( T_{*}-T \right ) = \left ( 1-\lambda \right ) T^\lambda + \lambda T^{\lambda-1} T_{*}$
    94 
    95 but then we would still have a non-linear term like $\lambda T^{\lambda-1} T_{*} \nabla T_{*}$
    96 
    97 We could write this as $\lambda T^{\lambda-1} 1/2 \nabla T_{*}^2$ and Taylor expand again to get $\lambda T^{\lambda-1} 1/2 \nabla \left ( - T + 2 TT_{*} \right )$
    98 
    99 but we've now done a Taylor expansion on a Taylor expansion... 
    100 
    101 
    102 Alternatively, we can rewrite the diffusion equation
    103 
    104 $\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \frac{\kappa_\parallel}{\lambda+1} \left ( \hat{b} \cdot \nabla T_*^{\lambda+1} \right )\right ]$
    105 
    106 
    107 
    108 and then perform a single Taylor expansion
    109 
    110 $\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \frac{\kappa_\parallel}{\lambda+1} \left ( \hat{b} \cdot \nabla \left (-\lambda T^{\lambda+1} + \left ( \lambda + 1 \right ) T^{\lambda}T_{*} \right )  \right ) \right ]$
    111 
    112 Switching to Einstein notation, we have
    113 
    114 $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \partial_i  n b_i b_j \partial j \left ( -\lambda T^{\lambda+1} + \left ( \lambda + 1 \right ) T^{\lambda}T_{*} \right )  $
    115 
    116 $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \partial_i  n b_i b_j \partial j \left ( -\lambda T^{\lambda+1} + \left ( \lambda + 1 \right ) T^{\lambda}T_{*} \right )  $
    117 
    118 Let's also take a moment to write $T_* = \phi T + \psi T'$  where $T'$ is the new temperature, and $\phi + \psi = 1$.  Backward Euler would have $\phi=0$ and $\psi=1$ where Crank-Nicholson would have $\phi=\psi=1/2$
    119 
    120 $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \partial_i  n b_i b_j \partial j \left ( -\lambda T^{\lambda+1} + \left ( \lambda + 1 \right ) T^{\lambda}\left ( \phi T + \psi T' \right ) \right )  $
    121 
    122 
    123 $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \partial_i  n b_i b_j \partial j \left ( \left ( \phi - \psi \lambda \right ) T^{\lambda+1} + \psi \left ( \lambda + 1 \right ) T^{\lambda} T' \right )   $
    124 
    125 
    126 $\partial_t T = \frac{\kappa_\parallel}{\lambda+1} \left [ \left ( \partial_i n b_i b_j \right )  \partial j \left ( \left ( \phi - \psi \lambda \right ) T^{\lambda+1} + \psi \left ( \lambda + 1 \right ) T^{\lambda} T' \right ) +  n b_i b_j \left ( \left ( \phi - \psi \lambda \right ) \partial_i \partial_j T^{\lambda+1} + \psi \left ( \lambda + 1 \right ) \partial_i \partial_j T^{\lambda} T' \right ) \right ]$
    127 
    128 
    129 Now if we write the equation as
    130 
    131 $\partial_t T = B_j \partial_j T^{\lambda+1} + C_j \partial_j T^\lambda T' + D_{ij} \partial_i\partial_j T^{\lambda+1} + E_{ij} \partial_i \partial_j T^\lambda T'$
    132 
    133 we get expressions for
    134 
    135 $\phi' = \frac{\left ( \phi-\psi\lambda \right )}{\psi \left (\lambda+1 \right )} $
    136 
    137 $B_j =  \phi' C_j $   
    138 
    139 $C_j =   \kappa_\parallel \psi \partial_i n b_i b_j $
    140 
    141 $D_{ij}=\phi'E_{ij}$
    142 
    143 $E_{ij} =   \kappa_\parallel \psi  n b_i b_j $
    144103
    145104We then need expressions for
     
    153112$\partial_i\partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{i}+\hat{j}} - T^{\lambda+1}_{\hat{i}-\hat{j}}-T^{\lambda+1}_{-\hat{i}+\hat{j}} + T^{\lambda+1}_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) +  \frac{T^{\lambda+1}_{\hat{i}} - 2T^{\lambda+1}_{0} + T^{\lambda+1}_{-\hat{i}}}{\Delta x^2}\delta_{ij}$
    154113
    155 $\partial_i\partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{i}+\hat{j}}T'_{\hat{i}+\hat{j}} - T^{\lambda}_{\hat{i}-\hat{j}}T'_{\hat{i}-\hat{j}}-T^{\lambda}_{-\hat{i}+\hat{j}}T'_{-\hat{i}+\hat{j}} + T^{\lambda}_{-\hat{i}-\hat{j}}T'_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) +  \frac{T^{\lambda}_{\hat{i}}T'_{\hat{i}} - 2T^{\lambda}_{0}T'_{0} + T^{\lambda}_{-\hat{i}}T'_{-\hat{i}}}{\Delta x^2}\delta_{ij}$
     114$\partial_i\partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{i}+\hat{j}}T'_{\hat{i}+\hat{j}} - T^{\lambda}_{\hat{i}-\hat{j}}T'_{\hat{i}-\hat{j}}-T^{\lambda}_{-\hat{i}+\hat{j}}T'_{-\hat{i}+\hat{j}} + T^{\lambda}_{-\hat{i}-\hat{j}}T'_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) $ $ + \frac{T^{\lambda}_{\hat{i}}T'_{\hat{i}} - 2T^{\lambda}_{0}T'_{0} + T^{\lambda}_{-\hat{i}}T'_{-\hat{i}}}{\Delta x^2}\delta_{ij}$
     115
    156116
    157117We can also write the equation as